The Helpless Angel in Charlotte Perkins Gilman’s The Yellow Wallpaper - Chalak Ghafoor Raouf; Helan Sherko Ali (International Journal of English Language and Translation Studies, 2018)
The paper analyzes Charlotte Parkinson Gilman's The Yellow Wallpaper from a feminist perspective. It reveals the reasons behind the existence of this literary text in the late 19th century. For this purpose, the paper presents Gilman's life as the background of the study, and then, it tries to find a link between her life as a woman and the life style of narrator in The Yellow Wallpaper. In this way, the paper theorizes the arguments with reference to both Gilman's life, and the sequences of events in The Yellow Wallpaper. During the lifetime of Gilman, majority of women suffered from being subject to men and male dominance which confined them into homes. Thereby, they were forbidden from their rights to work or to get knowledge or even to speak their minds. So, being affected by the miserable condition of women around her, Gilman wrote The Yellow Wallpaper in order to defend women in her society. Thus, the paper tries to demonstrate that Gilman uses her text as a tool to encourage and normalize women’s resistance to the patriarchal rules in their society that confined, oppressed, and dehumanized women. Gilman uses her protagonist in the text as a role model for women in her society who were oppressed, and left helpless. Throughout the text, Gilman tries to walk in the shoes of those women who never got a chance to be what they are and got broken at the end. Thus, the paper exposes the dystopian life style of the narrator so as to reach into a conclusion that the narrator's story is not more than Gilman's story which is presented to stand for women’s story in the late 19th century. The phrase "Helpless Angel" in this paper, thus, is symbolically presented so as to symbolize the helpless women in Gilman's time. The phrase is driven from one of the main patriarchal terms of the age which was The Angel in the House.